The Accuration of LiquidBased Cytology and HPV DNA Test Combination as Precervical Cancer Lesion Screening - Indarti, Junita; Pratama, Yuven S (Indonesian Socety of Obstetrics and Gynecology, 2017)
Objective: To investigate the accuracy of liquid-based cytology, HPV DNA test, and the combination of liquid-based cytologyband HPV DNA test, compared to histopathology as the gold standard of precervical cancer lesion screening. Methods: This was a cross-sectional study. The medical records of patients who came to the Women’s Health Clinic of Dr. Cipto Mangunkusumo Hospital during the period of July 2013 to December 2015 were evaluated. Results: The high risk type HPV DNA is detected in 76% CIN 1, 88.46% CIN 2, and 84.21 CIN 3 in histopathology results. The accuracy of liquid-based cytology; sensitivity 88.54%, specificity35.71%, PPV 75.89%, and NPV 57.69%. The accuracy of HPV DNA; sensitivity 81.25%, specificity 78.57%, PPV 89.66%, and NPV 64.71%. The accuracy of combination: sensitivity 94.79%, specificity 35.71%, PPV 77.12%, and NPV 75%. Conclusion: The addition of HPV DNA test increased the sensitivity from 88.54% to 94.79% because of decreasing of false negative of liquid-based cytology. This thing has showed that the combination of liquid-based cytology and HPV DNA test could the one of the option of precervical cancer lesion screening method, especially in secondary or tertier health center in Indonesia. Keywords: accuracy test, HPV DNA, liquid-based cytology, precervical cancer lesion, precervical cancer lesion screening